RELATIONSHIP BETWEEN PROBLEMATIC MOBILE PHONE USE AND SCHOOL WORK PARTICIPATION AMONG SECONDARY SCHOOL STUDENTS IN ENUGU STATE, NIGERIA - Ogbuabor, Columbus O. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Schoolwork participation is an essential component of the educational ecosystem of every society. However, engaging in schoolwork in many cultures has been fraught with many challenges, including the ever-increasing innovations in smartphone technology. The present study examined problematic mobile phone use as a variable that could account for the variations in schoolwork participation among secondary school students. Two hundred and fifty-two senior secondary school students from five public and private schools in Enugu state participated in the survey. They completed a self-report measure of the Schoolwork Engagement Inventory and Smartphone Addiction Scale-Short Version (SAS-SV). The simple regression analysis conducted on the data revealed problematic mobile phone use as a positive predictor of schoolwork participation. Most importantly, the result showed that problematic mobile phone use explained 21.1% of the variance in schoolwork engagement. The practical implications and recommendations are discussed.